2021
DOI: 10.1007/s10212-021-00557-x
|View full text |Cite
|
Sign up to set email alerts
|

Student dropout at university: a phase-orientated view on quitting studies and changing majors

Abstract: Student dropout can be conceptualized as a decision-making process, consisting of different phases. Based on previous literature on student dropout, decision-making, and action-phases, we proposed that the process of developing dropout intentions includes the following phases: non-fit perception, thoughts of quitting/changing, deliberation, information search, and a final decision. In the present cross-sectional study, we empirically investigated if the assumed phases can be distinguished from each other, if t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 66 publications
0
24
0
4
Order By: Relevance
“…Indeed, interview studies with study counselors (Patrzek et al, 2012(Patrzek et al, et al, 2012 and students of different semesters (Grunschel et al, 2013b) identified procrastination as a possible reason for forming dropout intentions. Two cross-sectional studies with students of different semesters also found a positive relationship between procrastination and dropout intentions (Bäulke et al, 2018(Bäulke et al, , 2021. However, it lacks longitudinal studies allowing conclusions on the temporal relations between procrastination and dropout intentions.…”
Section: Study Behavior and Study Satisfaction As Predictors Of Dropout Intentionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, interview studies with study counselors (Patrzek et al, 2012(Patrzek et al, et al, 2012 and students of different semesters (Grunschel et al, 2013b) identified procrastination as a possible reason for forming dropout intentions. Two cross-sectional studies with students of different semesters also found a positive relationship between procrastination and dropout intentions (Bäulke et al, 2018(Bäulke et al, , 2021. However, it lacks longitudinal studies allowing conclusions on the temporal relations between procrastination and dropout intentions.…”
Section: Study Behavior and Study Satisfaction As Predictors Of Dropout Intentionsmentioning
confidence: 99%
“…An individual may not invest time and energy in behavior (e.g., learning) to achieve this uncertain goal, but instead postpone study-related tasks (i.e., procrastination). Regarding study satisfaction, students thinking about dropping out might begin to see more negative aspects of their studies (i.e., mind-shift; Brandstätter et al, 2013; see also Bäulke et al, 2021). This can affect their study satisfaction negatively.…”
Section: Effects Of Dropout Intentions On Study Satisfaction and Procrastinationmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 15% of university dropouts in Germany remain unemployed after six months [ 7 ], but it needs to be mentioned that dropouts often wait to exmatriculate until they find a job, which leaves unemployment undetected [ 8 ]. This development seems even more relevant given the severe lack of academically qualified professionals in a wide range of sectors [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%